ANALISIS KECACATAN PROSES PRODUKSI CYLINDER HEAD GASKET - Mark, Wendry; Boni Sena; Kardiman (Universitas Muhammadiyah Metro, 2024)
combustion system, especially in the cylinder head gasket, which regulates the flow of fuel and air into the combustion chamber. A common problem is leakage due to imprecision, affecting compression pressure, engine performance, and potentially causing overheating. This research aims to analyze the temperature effects on cylinder head gaskets using the finite element method and to recommend appropriate thermal loads.The study employs a clinking method where a machine moves a ram to a die, pressing sheet metal to shape the gasket, followed by a blanking stage. Analysis is conducted using SolidWorks 2022. Results indicate that temperature significantly affects the gasket's strength. As temperature rises, the gasket's strength decreases. Stainless steel, the material used, expands with higher temperatures, altering dimensions and impacting the safety factor. The higher the temperature, the lower the strength and safety factors of the cylinder head gasket.This research highlights the crucial role of temperature in the design and material selection for cylinder head gaskets. Ensuring that gaskets can withstand thermal loads is essential for maintaining engine performance and preventing issues like overheating. By understanding the relationship between temperature and gasket strength, better materials and designs can be developed to enhance durability and reliability in internal combustion engines.